2007
DOI: 10.1021/cg060827q
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Monodisperse Tungstate MWO4 Microspheres (M = Pb, Ca):  Surfactant-Assisted Solution Synthesis and Optical Properties

Abstract: Nearly monodisperse PbWO4 and CaWO4 microspheres have been synthesized in large scale by a surfactant-assisted solution route, in which either sodium dodecyl benzenesulfonate (SDS) or cetyltrimethyl ammonium bromide (CTAB) is used. By controlling the solution reaction conditions, such as temperature, surfactant, and pH value, we can synthesize nearly monodisperse microspheres of tetragonal tungstate (MWO4, M = Pb, Ca) composed of subunits with different shapes. The diameters of these microspheres have been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(54 citation statements)
references
References 70 publications
(40 reference statements)
5
46
0
Order By: Relevance
“…The emission peaks at about 415 nm and 560 nm are agreement with the reported value [17,18]. Figure 4a-c show temperature-dependent luminescence spectra of the ZnS spheres prepared by aging at 160°C for different reaction time, such as 1 h, 3 h, and 10 h. From figure 4a, b and c, it can be seen that with increasing temperature from 35 K to room temperature, the luminescence intensity decreases dramatically, which is similar to reported previously [19]. 415 and 560-nm-centered emissions are observed in all the samples, which are defect related and assigned to self-activated luminescence of ZnS nanocrystallite [20].…”
Section: Resultssupporting
confidence: 89%
“…The emission peaks at about 415 nm and 560 nm are agreement with the reported value [17,18]. Figure 4a-c show temperature-dependent luminescence spectra of the ZnS spheres prepared by aging at 160°C for different reaction time, such as 1 h, 3 h, and 10 h. From figure 4a, b and c, it can be seen that with increasing temperature from 35 K to room temperature, the luminescence intensity decreases dramatically, which is similar to reported previously [19]. 415 and 560-nm-centered emissions are observed in all the samples, which are defect related and assigned to self-activated luminescence of ZnS nanocrystallite [20].…”
Section: Resultssupporting
confidence: 89%
“…3b-d Figure 4 show the luminescence spectra of the PbWO 4 particles measured at different temperatures. The emission peaks at about 430 nm is agreement with the reported value [9]. Figure 4a-c show temperaturedependent luminescence spectra of the PbWO 4 prepared by aging at 160 °C for different reaction time, such as 3 h, 6 h, and 10 h. From figure 4D, it can be seen that with increasing temperature from 35 K to 316K, the www.crt-journal.org luminescence intensity decreases dramatically.…”
Section: Resultssupporting
confidence: 85%
“…The progresses have demonstrated that it is possible to control the growth processes of nanocrystals and their nanoarchitectures with complex forms and different compositions [4,5]. The presence of organic additives or surfactants [6][7][8][9], self-assembled organic superstructures and templates with complex functionalization patterns [10] can direct the growth of inorganic crystals with controlled morphologies and architectures [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular, the fabrication of hierarchical and complex nano-/microstructures by the assembly of nanoparticles, nanorods, nanosheets, or nanobelts as building blocks at different levels has recently been proposed and partially realized. [7][8][9][10][11] To date, a variety of materials, such as oxides, [12][13][14] sulfides, [15,16] hydrates, [17,18] and other compounds, [19][20][21][22][23] have been prepared with controlled hierarchical/complex morphologies by various methods. In these fabrications, the hydrothermal method, as a typical solution-based approach, has proved to be an effective and convenient synthesis technique for preparing various inorganic materials with diverse morphologies and architectures.…”
Section: Introductionmentioning
confidence: 99%